2018
DOI: 10.3341/kjo.2017.0104
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Bispectral Index to Predict Eye Position of Children during General Anesthesia

Abstract: PurposeTo assess the relationship between eye position and anesthesia depth using the bispectral index (BIS) value, a parameter derived from electroencephalography data.MethodsWe investigated the relationship between BIS value and eye position in 32 children who underwent surgery for epiblepharon under general anesthesia. BIS values were recorded continuously throughout the procedure (from induction to awakening). Eye positions were video-recorded and analyzed after surgery. The vertical position of each eye w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Though few studies have described up-gaze eccentric eye-positioning under general anesthesia, there is paucity in literature regarding eccentric down positioning of eyes. 4,5,6,14 Few of the studies describing eye positioning under general anesthesia encountered down positioning of eyes. 4,6,14 Power et al in his study observed nal eye position in downward direcion under different depths of general anesthesia 14 in few patients but their number, depth of general anaesthesia, and down-scoring of eye position were never described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though few studies have described up-gaze eccentric eye-positioning under general anesthesia, there is paucity in literature regarding eccentric down positioning of eyes. 4,5,6,14 Few of the studies describing eye positioning under general anesthesia encountered down positioning of eyes. 4,6,14 Power et al in his study observed nal eye position in downward direcion under different depths of general anesthesia 14 in few patients but their number, depth of general anaesthesia, and down-scoring of eye position were never described.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors have described eccentric positioning of eyes under GA in upgaze. 4,5,6,12 Power et al while studying the depth of anaesthesia in young adults via sevo urane induction compared eye signs with EEG polysomnography and showed that, the deepest level of sleep was reached on an average 3 minutes before the onset of eccentric ocular positioning thereby suggesting that eccentric eye movements may occur even when a patient appears satisfactorily anesthetized. 14 Rossiter reported an incidence of 8% which increased up-to 18% without the use of muscle relaxants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positioning principle is shown in Fig. 1 [17]. The left and right signal receivers are horizontally placed at the upper left and upper right of the positioning area, and the coordinate positions of the two signal receivers are known, and the distance d between the receivers can be measured or calculated.…”
Section: Methodsmentioning
confidence: 99%